Assessment of the N-Alkylamide Content and Volatile Profiles in Two Cultivars of Acmella oleracea (L.) R.K. Jansen Grown in Aquaponics - Marta Ferrati; Beatrice Bartolini; Giulio Lupidi; Lorenzo Freddi; Valentina Bolletta; Marco Cespi; Rita Giovannetti; Marco Zannotti; Riccardo Petrelli; Filippo Maggi; Eleonora Spinozzi (Plants)
Acmella oleracea (L.) R.K. Jansen, also called jambù, is a medicinal and aromatic plant native to the Brazilian Amazon rainforest and phytochemically characterized by N-alkylamides with spilanthol as the main active compound. Jambù recently attracted the interest of many companies because of its wide range of pharmaceutical, nutraceutical, and cosmetic applications. In this context, it is desirable to identify eco-friendly cultivation methods that not only minimize the environmental footprint but also support the biosynthesis of the plant’s valuable bioactive compounds. The zero-discharge approach of aquaponics makes this growing system an eco-friendly and sustainable production strategy for crops. Thus, a greenhouse experiment was conducted on two jambù cultivars, i.e., cv ‘purple’ and cv ‘yellow’, grown in aquaponic and hydroponic systems. The objective was to compare their contents of N-alkylamides, their numbers of capitula, which are the main source of these bioactives, and their volatile profiles. The results highlighted differences between the two cultivars and among plants harvested at different periods. Interestingly, aquaponics yielded plants with a high N-alkylamide content, which was comparable to that obtained with hydroponics. Overall, this study highlighted the feasibility of adopting aquaponics to grow A. oleracea, paving the way for circular economy-based and sustainable agricultural practices.